Information and communication technology (ICT), economic indicators, and banking sector indicators: Its impact on the ASEAN-5 countries' banking sector performance: An analysis - Dominguez, Piero Antonio D. (Animo Repository, 2022)
Information and Communication Technologies (ICT) enables users to receive and use information efficiently and effectively, contributing to business operations and communication among society. During Industry 4.0, growth and development of technologies that contribute to information sharing improved efficiency among businesses from different industries. However, there have been mixed findings on whether these contribute to the profitability among banks in the financial sector. Thus, this research investigates the effects of Information and Communication Technologies (ICT), as well as economic and bank sector indicators, on the profitability of banks. The research utilizes panel regression analysis and focuses on data from the ASEAN-5 countries (Indonesia, Malaysia, Philippines, Thailand, and Vietnam) from 2010 to 2015. Findings from the analysis suggest that mobile cellular subscriptions and individuals using the internet have shown consistently positive effects, whereas imports of ICT goods showed negative effects on bank profitability. Likewise, domestic credit to the private sector showed consistent negative effects on profitability, while bank cost to income ratio only significantly decreased one (1) profitability indicator. In assessing the results, the researchers recommended further analysis of the study with more recent data. Suggestions were also devised for financial institutions that are considering the use of ICT in their operations.Keywords: Information and Communication Technology, Industrial Revolution 4.0, Panel Regression